Clove production rising - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
After years of decreasing production the clove trade in Zanzibar is firming up again. In the 1960s, the island produced 20,000 tonnes of cloves annually. Then, production declined to an absolute minimum of 204 t in 1998. Their major customer,...